Application of Fuzzy Logic and PID Controller for Mobile Robot Navigation - Babunski, Darko; Berisha, Jakup; Zaev, Emil; Bajrami, Xhevahir (IEEE, 2020)
Mobile Robot navigation in real environment, detecting and avoiding static and dynamic obstacles is still a challenging task even counting new technology development. This consists, on methods and algorithms applied in order to achieve most optimal results. We present application of Fuzzy Logic Controller (FLC) and PID controller, which will deal with, signal processing of three sensors as inputs of FLC and two outputs which are left and right motors as actuators. Outputs from FLC will be sent to PID controller in order to get better and more accurate results for mobile robot navigation respectively more exact robot movement. In this paper is presented, a navigation of the mobile robot via FLC and PID controller.
Keywords: component, navigation, obstacle avoidance, ultrasonic sensors, mobile robot, FLC, PID